PENGARUH PEGGUNAAN TEKNIK TALKING CHIP TERHADAP HASIL BELAJAR IPA FISIKA SISWA KELAS VII SMPN 1 IV JURAI KABUPATEN PESISIR SELATAN - Arif Budi Yanda (Universitas Negeri Padang, 2013)
The purpose of this research was to investigate the effect of using of talking chip technique to student learning outcomes at grade 7 SMPN 1 IV Jurai Pesisir Selatan. Research method that used is quasi experimental with randomized control group only design. The population is student of grade 7 SMPN 1 IV Jurai listed in the academic year 2012/2013. Cluster random sampling technique was used in this research, and choosed 7.3 as the control group and 7.1 as the experiment group. Data is the learning outcome in the cognitive, affective and psychomotor aspect. Instrument was the achievement test on the cognitive, observation sheet for affective and scoring rubric on psychomotor. This research found that learning outcomes in physics using technique talking chip higher than the other group. Conclusion of research was the hypothesis there is a significant influence on using of techniques talking chips on student’s learning outcomes in science physics at grade 7 SMPN 1 IV Jurai Pesisir Selatan acceptable real level of 0.05. Keyword : Talking Chip, Learning Outcomes